NGHIÊN CỨU NHÂN GIỐNG IN VITRO VÀ KHẢO SÁT HỢP CHẤT ALKALOID ROTUNDINE TỪ CÂY BÌNH VÔI (STEPHANIA ROTUNDA LOUR - Nam, Trịnh Ngọc; Vinh, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
RESEARCH THE MICROPROPAGATION IN VITRO AND DETECTION ROTUNDINE OF STEPHANIA ROTUNDA LOUR. Binh voi (Vietnamese name), Stephannia Rotunda Lour is a wild herbal species often found in jungles of Binh Thuan, Ninh Thuan, Lam Dong and Dong Nai. This is a valuable medicinal herb that can treat some diseases, such as: enteritis, stomachache, especially depression. Recently, because of the exploitation and destruction of jungles, the Binh Voi will be extinct in near future is undeniable. Therefore, using preservation and restoration techniques is necessary and in vitro is a efficient one. Media have 3 - 10 mg/l of 2,4-D formed callus from cuttings of the Stephania rotunda Lour. The medium having higher concentration of minerals had a higher ability of forming callus. Having 1 mg/l BA and 0,2 mg/l of NAA in the medium stimulated the forming of shoots from buds on cuttings. The substance alkaloid rotundine, which can cure the depression, appeared on the stem, bulb (natural) and callus (in vitro) samples. And the highest concentration of alkaloid rotundine is from bulb samples.